COLLABORATIVE E-LEARNING BERBASIS WEB PADA MATA KULIAH EXTENSIVE READING - Riana Eka Budiastuti; Yunita Nugraheni (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The application of e-learning nowadays is being the trend in education field. Unfortunately not many lecturers in English Education Department of Unimus is actively engaged in the application of e-learning. However, if it is used optimally, it will bring much benefit to both students and lecturer, because this can be collaborated with the collaborative learning method that enables the application of student-centered learning in the classroom. This study develops web-based collaborative e-learning in Extensive Reading subject. This Research and Design study aims to design and develop web-based collaborative learning. Besides, it also will describe the implementation of the product in the class of Extensive Reading by observing the result of the student’s assessment. The result of the study showed that students’ achievement in Extensive Reading is increased by 18.55%. According to the questionnaire and interview, it can be concluded that both students and lecturer find it easy and helpful by the existence of this collaborative e-learning.Keywords: collaborative learning, e-learning, mata kuliah extensive reading